Factors in the prioritization of information needs among Hong Kong Chinese breast cancer patients - Ann W. Y. Bei; M T Lai; K C Choi; Polly W. C. Li; Winnie K. W. So (Asia-Pacific Journal of Oncology Nursing, 2015)
Objective: The study aims to examine the prioritization of information needs in breast cancer patients, using the Information Needs Questionnaire (INQ); and to identify the demographic and clinical characteristics associated with that prioritization. Methods: A cross-sectional exploratory study was conducted, by means of consecutive sampling. The INQ was used to examine participants′ preferences on information needs. Their demographic and clinical characteristics were collected by means of a structured questionnaire and review of medical records. Backward multivariable logistic regression analysis was performed to examine the association between prioritization of patients′ information needs and their demographic and clinical characteristics. Results: A total of 275 breast cancer patients took part in the analysis. Of the nine INQ items, most participants ranked as their top four needs information about the likelihood of a cure (79%), extent of the disease (76%), treatment options (55%), and family risk of developing breast cancer (51%). Certain demographic and clinical characteristics-religious belief, whether living alone or not, household income, educational level, and time since cancer diagnosis-influenced patients′ prioritization of information needs. Conclusion: Understanding and meeting the information needs of breast cancer patients are crucial to improving their quality of care. Different patients are likely to have different priorities in information needs according to their demographic and clinical characteristics. An awareness of these associated factors will allow better tailor-made educational interventions to be provided to meet patients′ individual needs in a more adequate way.